2016
DOI: 10.1021/acsami.6b06780
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Migration of Neural Stem Cells by Microglia Grown on a Three-Dimensional Graphene Scaffold

Abstract: One of the key challenges in engineering neural tissues for cell-based therapies is to develop a biocompatible scaffold material to direct neural stem cell (NSC) behaviors. One great advantage for a scaffold would be to induce NSC migration toward pathological sites during regeneration and repair. In particular, the inflammatory responses in the pathological zone, which are mainly mediated by microglia in the central nervous system, affect the repair capacity of NSCs through NSC migration. Recently, graphene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Various 2D and 3D architectures such as graphene nanofibers or foams have also displayed promise for neural tissue engineering . 3D GO nanofibers (GO‐NFs) have shown greatly enhanced growth and development of primary motor neurons, assisted by electrical stimulation of the cells via the conductive GO‐NFs .…”
Section: Interactions Between Graphene Derivatives and Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various 2D and 3D architectures such as graphene nanofibers or foams have also displayed promise for neural tissue engineering . 3D GO nanofibers (GO‐NFs) have shown greatly enhanced growth and development of primary motor neurons, assisted by electrical stimulation of the cells via the conductive GO‐NFs .…”
Section: Interactions Between Graphene Derivatives and Tissuesmentioning
confidence: 99%
“…3D GO nanofibers (GO‐NFs) have shown greatly enhanced growth and development of primary motor neurons, assisted by electrical stimulation of the cells via the conductive GO‐NFs . Microglia grown in 3D graphene foams produced conditioned medium (CM) that promoted cell adhesion and neurosphere formation, which does not occur when microglia are grown on 2D graphene films . 3D structures present many properties that are uniquely different than their 2D counterparts and could be even better for neural tissue engineering and regenerative medicine.…”
Section: Interactions Between Graphene Derivatives and Tissuesmentioning
confidence: 99%
“…14 Researchers have demonstrated that 3D structured graphene, compared to 2D, provides larger accessible specific surface areas, interconnected conductive structure and unique surface microstructure, 120,121 which might improve cell growth and differentiation. 122,123 To further compare the compatibility of 3D and 2D structured graphene, Jiang et al 124 synthesized 2D films and 3D foams of graphene and reported that 3D structured foams are more beneficial for migration of neural stem cells. Indeed, the 3D graphene foam could enhance cell migration through stromal-cell derived factor-1α/CXCR4 signaling pathway, which is essential for the cell migration.…”
Section: Dimensionmentioning
confidence: 99%
“…Nanostructures have evolved as multidisciplinary applications by combination with materials as an advanced architecture to develop functional substitutes for various proposes such as wound dressing [4][5][6], tissue engineering [7][8][9][10][11], and biomedical applications [12][13][14]. Neuroscience, related to the retina is one of the most exciting fields where nanostructures with modified properties serve as scaffolds to promote and facilitate the migration and adhesion of the cells [15].…”
Section: Introductionmentioning
confidence: 99%